2019
DOI: 10.1556/0806.46.2018.70
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress induces genotype-specific DNA hypomethylation in ZmEXPB2 and ZmXET1 genes in maize

Abstract: Maize, a moderately salt sensitive crop, first experiences osmotic stress that cause reduction in plant growth under salt stress. Fluctuation in cell wall elongation is one of the reasons of this reduction. Along with others, two important proteins expansins and xyloglucan endotransglucosylase are involved in regulation of cell wall elasticity, but the role of epigenetic mechanisms in regulating the cell wall related genes is still elusive. The present study was conducted with the aim of understanding the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The upregulation of EXPB2 gene in Solanum pennellii under drought stress conditions indicated towards the strong association between EXPB2 gene and drought stress tolerance (Egea et al 2018). Interestingly, the involvement of epigenetic mechanisms at both DNA methylation and histone acetylation levels in the regulation of EXPB2 gene in maize against salt stress have already been reported (Li et al 2014;Kaleem et al 2019). Li et al (2014) revealed an increase in H3K9 acetylation was associated with the ZmEXPB2 up-regulation under salt stress conditions.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…The upregulation of EXPB2 gene in Solanum pennellii under drought stress conditions indicated towards the strong association between EXPB2 gene and drought stress tolerance (Egea et al 2018). Interestingly, the involvement of epigenetic mechanisms at both DNA methylation and histone acetylation levels in the regulation of EXPB2 gene in maize against salt stress have already been reported (Li et al 2014;Kaleem et al 2019). Li et al (2014) revealed an increase in H3K9 acetylation was associated with the ZmEXPB2 up-regulation under salt stress conditions.…”
Section: Introductionmentioning
confidence: 84%
“…Li et al (2014) revealed an increase in H3K9 acetylation was associated with the ZmEXPB2 up-regulation under salt stress conditions. Similarly, ZmEXPB2 gene up-regulation by the DNA hypomethylation in this gene induced by salt stress in maize has been reported (Kaleem et al 2019). But the ZmEXPB2 gene regulation by DNA methylation shift in maize under drought stress need to be explore.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations